Development of technique through the mini trampoline in hands-free exercises in women's artistic gymnastics (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2013)
SUMMARYThe overall objective of this research project was to design a teaching strategy for developing technique through the use of mini trampolines in hands-free exercises in artistic gymnastics for girls at the Prometeo training school at the University of Pamplona. Throughout the history of artistic gymnastics, many authors have followed pedagogical criteria in their works to differentiate between different gymnastic movements. However, our foray into this subject has sought to highlight the idea of the emergence, evolution, diversification, and variety of trends within today's physical culture as a legacy of historical events in our field. The current eclectic nature of physical education in the education system brings together the different trends that have historically manifested themselves in each of the gymnastics systems. This research took a sample of 39 girls aged between 6 and 12 from different educational institutions and the University of Pamplona's gymnastics training school. The sample selected consisted of 10 girls aged between 9 and 12 from the gymnastics training school at the University of Pamplona. In this way, fundamental errors described in the problem description were corrected and reinforced in accordance with the pedagogical intervention that was carried out, where specific planning by microcycles was applied and, through specific tests and their correct descriptive and inferential statistical analysis, it was generally verified with results of p: 0.005, indicating the reliability of the proposed strategy, which should serve as a guide for the gymnastics departments at the University of Pamplona and for the training processes used by the Northern Santander Department League.